Machining and its challenges on bio-fibre reinforced plastics: A critical review. (August 2018) - Vinayagamoorthy, R; Rajmohan, T
Bio-degradability and sustainability have become major objectives in the field of materials engineering. Due to this, the utilisation of natural reinforcement is gaining immense attention among composite researchers. Among the different composites, polymeric composites are used as structural components. In the present day investigations, bio-elements are majorly utilized as reinforcements due to their properties and bio-degradability. Although polymeric components are manufactured in the shape of the final component, they need secondary processing to make it suitable for assembly. Hence, a review on machining and associated investigations on bio-composites would help the composites industries and upcoming researcher to know the scope of research and for selection of apt machining conditions. This review gives a detailed insight on the various machinability factors and their measurement, influence of machining parameters on the machinability and optimum conditions during machining of bio-composites. In addition, this review also presents about the importance of bio-fibre under various situations of machining and untraditional machining methods used for bio-composites.